Reframing Penal Policy: Incorporating Community-Based Norms into Indonesia’s National Legal Architecture - Rika Kurniasari Abdulgan; Abdy Yuhana (International Journal of Educational Review, Law And Social Sciences (IJERLAS), 2025)
This article examines the urgency of integrating community-based norms into Indonesia’s national penal policy as part of legal reform in the post-modern legal era. The current criminal justice system in Indonesia still largely reflects a centralized and positivistic legal tradition inherited from colonial structures, resulting in limited accommodation of local wisdom and restorative mechanisms that live within indigenous and local communities. This study addresses two primary research questions: first, how community-based norms function within Indonesia’s socio-legal landscape; and second, how such norms may be incorporated into the national penal policy framework without undermining legal certainty and constitutional principles. This research employs a normative-juridical method with conceptual and comparative approaches, utilizing statutory regulations, legal doctrines, scholarly articles, and socio-legal perspectives as primary sources. The findings demonstrate that community-based norms, particularly those emphasizing restorative justice, social harmony, collective accountability, and consensus-based dispute resolution, possess significant potential to strengthen Indonesia’s criminal law reform agenda. The novelty of this article lies in its proposal of a hybrid penal policy model that systematically integrates local customary mechanisms into formal criminal justice institutions through legal recognition, judicial discretion, and participatory governance. Academically, this study contributes to contemporary discourse on legal pluralism and penal reform by offering a contextual framework for harmonizing state law with indigenous normative systems in Indonesia.